2018
DOI: 10.1002/uog.19098
|View full text |Cite
|
Sign up to set email alerts
|

Vasa previa screening strategies: decision and cost‐effectiveness analysis

Abstract: Within the baseline assumptions, transvaginal ultrasound screening for vasa previa appears to be most cost-effective when performed among IVF pregnancies. However, both IVF and ultrasound-indicated screening strategies fall within contemporary willingness-to-pay thresholds, suggesting that both strategies may be appropriate to apply in clinical practice. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
(63 reference statements)
1
31
0
1
Order By: Relevance
“…5,6 The present report supports previous observations that IVF is a risk factor for VP, and transvaginal ultrasound screening for VP appears to be most cost-effective when performed among IVF pregnancies. 7 Jauniaux et al 8 found an incidence of bilobed and succenturiate-lobed placenta of 22% in the IVF group compared with 6% in the control group. Abnormal umbilical cord insertion with normal placental morphology has been associated with IVF.…”
Section: Discussionmentioning
confidence: 96%
“…5,6 The present report supports previous observations that IVF is a risk factor for VP, and transvaginal ultrasound screening for VP appears to be most cost-effective when performed among IVF pregnancies. 7 Jauniaux et al 8 found an incidence of bilobed and succenturiate-lobed placenta of 22% in the IVF group compared with 6% in the control group. Abnormal umbilical cord insertion with normal placental morphology has been associated with IVF.…”
Section: Discussionmentioning
confidence: 96%
“…Velamentous umbilical cord insertion is also related to the occurrence of vasa previa . Therefore, in patients with velamentous umbilical cord insertion, low‐lying placenta, or abnormal placental morphology, the diagnosis of vasa previa must be considered . The American College of Obstetricians and Gynecologists also recommends the use of color Doppler in patients who are at a high risk for vasa previa .…”
Section: Discussionmentioning
confidence: 99%
“…RANZCOG recommendation three defines vasa praevia as fetal vessels that run through bare membranes that lie on or are within 20 mm of the cervical IOS (Table ). In the survey, only 29% of sonographers used this definition (Figure ) indicating an unfamiliarity of the threshold measurement recommended in the literature to quantify a vasa praevia.…”
Section: Discussionmentioning
confidence: 99%
“…2,11 A low-lying placenta in the mid-trimester ultrasound is defined as the lower placental edge being 20 mm or less from the cervical IOS. 2,8,13,15 From the survey, 99% of participants do this measurement; however, there was a disparity in the range of measurements used by sonographers, and only 51% of participants used the commonly accepted measurement ( Figure 4). When a low-lying placenta is identified transabdominally, sonographers should proceed to a transvaginal scan to improve diagnostic accuracy of their measurement.…”
Section: Figurementioning
confidence: 99%